QUALITY OF LIFE, FUNCTIONALITY, AND SELF-CONCEPT OF PEOPLE POST-DISCHARGE FROM LEPROSY - Cibelly Nunes Fortunato; Jordana de Almeida Nogueira; Karen Krystine Gonçalves de Brito; Ana Cristina de Oliveira e Silva; Valéria Peixoto Bezerra; Micheline da Silveira Mendes; Maria Eliane Moreira Freire (Universidade Federal do Paraná, 2024)
Objective: to evaluate the quality of life, functionality, and self-concept of people after discharge from leprosy. Methods: This was a cross-sectional epidemiological study carried out in a reference institution for leprosy in Paraíba, Brazil, from May to August 2021. Four instruments were used for sociodemographic and clinical characterization, assessment of quality of life, functionality, and self-concept. The data was analyzed using Pearson's chi-square, Fisher's exact, Mann-Whitney, and Kruskal-Wallis tests. Results: 131 people took part, of whom 86 (65.6%) were male and 72 (55%) were aged between 41 and 60. There was a negative impact on health-related quality of life among those with no schooling and low family income. Limitation of functionality in those who do not practice physical activity, are affected by neuritis, and have some degree of physical disability. However, high self-concept. Conclusion: It is essential to train professionals and organize assistance measures in the face of longitudinal and interdisciplinary care in this therapeutic phase.